Diagnóstico das infecções relacionadas a cateter em recém-nascidos e epidemiologia molecular dos Staphylococcus spp. isolados - Riboli, Danilo Flávio Moraes [UNESP] (2013)
Catheter-related bloodstream infections (CR-BSIs) have become the most common cause of healthcare-associated bloodstream infection and are associated with substantial morbidity and mortality and excess hospital costs. These infections include device colonization by microorganisms, exit site infection, and microbiologically confirmed device-related bloodstream infection. Semi-quantitative culture is used to determine the presence of microorganisms on the outer surface of the catheter, whereas quantitative culture also isolates microorganisms present inside the catheter. The objectives of this study were to compare the semi-quantitative and quantitative techniques for the diagnosis of CR-BSIs in newborns hospitalized in the neonatal ICU of HC-FMB, and to determine the incidence density and risk factors for these infections. In this study, 584 catheter tips from 399 patients seen between November 2005 and June 2012 were analyzed. The incidence density of CR-BSI varied according to newborn weight, with an incidence of 3.44/1000 catheter days in newborns <1,000 g and of 2.83/1000 catheter days in newborns >2,501 g. The sensitivity of the semi-quantitative and quantitative techniques was 72.7% and 59.3%, respectively, and specificity was 95.7% and 94.4%. The diagnosis of CR-BSI based on PFGE analysis of similarity between strains isolated from catheter tips and blood cultures showed 82.6% sensitivity and 100% specificity. Coagulase-negative staphylococci (CoNS) were the most frequently isolated microorganisms (75.9%), including S. epidermidis as the most prevalent species (65.5%), followed by S. haemolyticus (10.3%), yeasts (10.3%), K. pneumoniae (6.9%), S. aureus (3.4%), and E. coli (3.4%). Oxacillin resistance was observed in 90.9% of the CoNS isolated from cases of CR-BSI. SCCmec type III was detected in 55% of the isolates and the icaABCD operon in 59%. The oxacillin MIC was ≥0.5 μg/mL for most strains and the vancomycin MIC was ...